Experimental Study on the Active Earth Pressure of Narrow Cohesionless Backfills against Rigid Retaining Wall under the Translation Mode - Li-Wei Xu; Yu-Jian Lin (Advances in Civil Engineering)
In engineering, the new retaining walls are often constructed near the existing structure owing to the space limitation. The backfill behind the retaining wall is narrow, which causes an overestimation in the active earth pressure by using Coulomb’s earth pressure theory. In previous studies, experimental observations for the failure modes of narrow backfills are still rare. To confirm the failure mode of the narrow backfill, the experimental method and the geotechnical particle image velocimetry method are employed to observe the active failure process of the cohesionless narrow backfill with various widths under the translation mode. The experimental results revealed that the decrease in the length of the backfill width led to the increase in the inclined angle of the sliding surface. When the backfill width was sufficiently small, the sliding surface developed from the wall toe to another wall face, and then another sliding surface occurred as a reflection. In addition, the active earth pressure of the narrow backfill is significantly smaller than that calculated using Coulomb’s method. The active failure calculation models are established based on the experimental results. The active earth pressure of the narrow cohesionless backfill under the translation mode is derived by using the limit equilibrium methods. The proposed method was validated by comparing with the previous method and the experimental data.